FACTORS INFLUENCING INFORMATION TECHNOLOGY-BASED ADMINISTRATIVE SERVICES AT THE AMBON RELIGIOUS TRAINING CENTER - Titarsole, Kezia Risly; Pattimukay, Hengky V. R.; Patty, Julia Th. (PUBLICUS : JURNAL ADMINISTRASI PUBLIK, 2024)
This research is a qualitative study aimed at evaluating the quality of information technology-based administrative services and identifying influencing factors at the Ambon Religious Training Center. The background of this research stems from constraints in human resources, limited management of administrative technology, and inadequate information technology infrastructure. Involving seven key informants, the research utilizes data collection techniques such as interviews and observations. The findings reveal that information technology-based administrative services at the Ambon Religious Training Center have not yet reached an optimal level of satisfaction. Evaluation is conducted using indicators of transparency, participation, and efficiency. Inhibiting factors involve limitations in human resources management of administrative technology, while supporting factors include efforts to improve information technology infrastructure. The implications of these findings can serve as a basis for designing strategies to enhance information technology-based administrative services in similar institutions, with the hope of improving transparency, participation, and efficiency in such services. This research provides a significant contribution to understanding the dynamics of implementing information technology in the context of religious administration.